Innate responses to conspecific and heterospecific alarm cues in the endangered eastern cape redfin Pseudobarbus afer. Issue 5 (25th November 2019) - Magellan, Kit; Booth, Anthony J.; Weyl, Olaf L. F.
Abstract: We examined innate responses to conspecific and heterospecific alarm cues in a small cyprinid minnow, the Eastern Cape redfin Pseudobarbus afer . We found that redfins respond to conspecific skin extract, which contains alarm chemicals, and showed that their preferred response is to hide in refugia. Redfins also respond to skin extract from an allopatric, distantly related minnow species, the chubbyhead barb Enteromius anoplus indicating that neither sympatry nor close phylogenetic relationships are necessary for recognition of heterospecific alarm cues. Although both conspecific and heterospecific alarm cues induced similar responses, the response to heterospecific cues was less intense. This may be explained by a trade‐off between selection to maximise threat recognition and selection to avoid the costs of responding to irrelevant cues, or by differences in chemical structures of alarm cues between species. These findings have implications for the conservation of this Endangered fish species and for freshwater fishes throughout Africa.